Pelatihan Pembuatan Kombucha Nanas Probiotik untuk Peningkatan Pengetahuan Kader PKK dan Posyandu di Desa Tambakmekar, Kabupaten Subang - Purkon, Dicki Bakhtiar; Trinovani, Elvi; Kusmiyati, Mimin; Pratama, Arvenda Rezky; Ansyirohanisa, Ansyirohanisa; Fatimah, Cucu; Syahla, Nizella; Fitria, Yefi; Al-Alifa, M. Rasya; Ulya, Cut Zidda; Septiani, Mitha Azalia; Fadhlillah, Faizah Min (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Tambakmekar Village, Jalancagak Subdistrict, Subang Regency, is one of the pineapple production centers in West Java, yet its utilization remains limited, resulting in low economic value. On the other hand, the community partners, consisting of PKK and Posyandu cadres, face health problems such as high risks of hypertension and blood glucose levels, as well as limited knowledge about probiotic functional foods. This Community Partnership Program (PKM) aimed to improve the knowledge and skills of cadres through training on the production of probiotic pineapple-based kombucha, health education, and simple health checks (blood pressure and blood glucose). Methods: The methods used included lectures, practical demonstrations, mentoring, and evaluation of knowledge using pre-test and post-test. Results: The average knowledge score of participants increased from 64.2 (pre-test) to 77.5 (post-test), representing a relative improvement of approximately 20.7%. Furthermore, participants were able to practice pineapple kombucha production independently and received an educational booklet as a reference material. The program outputs included a booklet, video documentation, and a manuscript for an academic article. Conclusions: This activity successfully enhanced the capacity of PKK and Posyandu cadres while promoting the use of local pineapple as a functional food with health benefits and potential economic value.